PROSPEK WANITA KARYA DI INDONESIA - Iswatiningsih, Daroe (Jurnal Bestari, 1994)
Women, who are as human being are as human resources in developing country, have the same rights and oppurtunities as men's. Therefore, their roles and potency must be maximized and be aimed at developing human resources